A eficácia horizontal imediata do direito social ao lazer nas relações privadas de trabalho - Calvet, Otavio Amaral (2005)
The Constitutional rules have immediate judicial force demonstrating the binding effects of the power of the Federal Constitution. The concrete appliance of the constitutional principles must be done by the method of ponderation of interests emphasizing the value of principle of dignity of the human person in the Brazilian legal system. The fundamental rights express superior values, which are included the social rights with immediate effect according the their density legislation and they empower all the fundamental rights of the presumption of this bindness. Such rights have a objetive dimension and another subjective. One which determines the reinterpretation of the legal system, acting in the control of the constitutionality and atributing revogatory effectiveness of previous infraconstitutional rules and guides the conduct of the State and its private entities, erradiating to private relations too. This side recognizes the subjective negative legal position (preventing from damages) and other, with the respect to the promotion of these rights, observing the "reserve of the possible". The leisue is a social right of all of the workers, either subordinated or not, having two aspects: economical and human. It is recognized to all works the need of a limitation of the working hours and the riths of exercing leisure. This implies an alteration of interpretation of the previous institutes of our infraconstitutional system and in the conduct of the contracting party to a service. It also recognizes to the worker the subjetive position to obtain always the judicial order with occasional moral damage when its value is harmed proportioned to the employees's economical dependency, whether in the employment relationships or in other private work relations